2000
DOI: 10.1161/01.str.31.9.2236
|View full text |Cite
|
Sign up to set email alerts
|

CO 2 Reactivity Measured by Perfusion MRI During Transient Focal Cerebral Ischemia in Rats

Abstract: Background and Purpose-CO 2 response was examined in rats undergoing 60 minutes of middle cerebral artery occlusion (MCAO) and 4.5 hours of reperfusion. Because it is not clear whether the vasoreactivity improves during reperfusion in parallel with tissue recovery, CO 2 response was determined spatially resolved, sequentially in the initially ischemic but later recovered areas and in the permanently damaged areas. Methods-Apparent diffusion coefficient (ADC) maps were calculated from diffusion-weighted images,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…The hippocampus, especially the cornu ammonis area 1 (CA1) subregion, is known for its susceptibility to ischemia (41) and low capillary density (42), with a low basal blood flow rate (14). The attenuated increase in hippocampal CBF in response to hypercapnia is in line with previous observations using BOLD MRI (34), and might be an indicator for a lower basal vasoreactivity as one possible factor determining higher susceptibility to ischemic damage (43).…”
Section: Discussionsupporting
confidence: 72%
“…The hippocampus, especially the cornu ammonis area 1 (CA1) subregion, is known for its susceptibility to ischemia (41) and low capillary density (42), with a low basal blood flow rate (14). The attenuated increase in hippocampal CBF in response to hypercapnia is in line with previous observations using BOLD MRI (34), and might be an indicator for a lower basal vasoreactivity as one possible factor determining higher susceptibility to ischemic damage (43).…”
Section: Discussionsupporting
confidence: 72%
“…In addition, the majority of previous studies has been more concerned with cerebral vasoreactivity, i.e. the response to CO 2 or acetazolamide, rather than CA [7, 8], and it is now increasingly accepted that CA and CR are in fact two distinct processes that may be dissociated [14]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether dynamic CA remains impaired following cerebral infarction. Recent reports in animal models of cerebral ischaemia have suggested that despite normalisation of the cerebral metabolism after reperfusion, those areas with the most severe ischaemic damage have persistently impaired CR, whereas in less ischaemic areas CR gradually improves with time [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Classifying patients according to the BHI cut-off of 0.69 [25], only 1 out of 13 patients (8%) with impaired cerebrovascular reactivity had a good clinical recovery, obtained by 41 out of 57 patients (72%) with normal cerebrovascular reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the correlation of higher values of BHI with good clinical recovery leads to consider the importance of general factors for cerebral blood flow regulation that, in turn, seem to be able to influencing the prognosis of patients with partial anterior circulation infarct. In the absence of major arterial severe stenosis, an impaired CVR may reflect an increased rigidity of the arteriolar walls [25] or a poor efficiency of collateral circulation [32] and has been associated with conditions related to an increased risk of stroke. In fact, decreased CVR has been observed in patients with hypertension, diabetes mellitus and smoking [33,34].…”
Section: Discussionmentioning
confidence: 99%